CLASSIFICATION OF UNFAVORABLE OUTCOMES OF THE PERI-OPERATIVE PERIOD - D. V. Sаdchikov (Вестник анестезиологии и реаниматологии, 2019)
The object of research in the field of anesthesiology and intensive care is the functional systems of the host; this research includes original tasks, elaboration and making certain decisions especially for critically ill patients where as a rule the outcome of anesthesia and intensive care depends not only on the special professional skills but moral and ethic features of the doctor. The main feature of biomedical systems is that the human body is the system which is complex, open and stochastic, and if the man is ill it is especially complex. And the major part of information about the patient is non-verbal; so the classification is an important component providing an impact on the treatment outcome. If the principles of information classification are properly used, the doctor is fully armed for analyzing, comprehending, adopting, assessing and solving the task. It also facilitates the dissemination of acquired knowledge and experience among other specialists.